Assessment of eucalypts wood lignin content by analytical pyrolysis, comparison with Klason and total lignin contents - Alves, Ana; Cisneros, Esteban F.; Balmelli, Gustavo; Marcucci Poltri, Susana Noemi; Rodrigues, Jose (Taylor and Francis, 2022)
Analytical pyrolysis can be used to determine the lignin content (Py-lignin) in eucalypt woods with a precision (0.37%) similar to the wet reference methods. Good correlations were found between the Py-lignin results and Klason (94%) and total lignin contents (95%). Besides apparent species-specific deviations, an average difference of 1.3% compared to the total lignin content was observed, well below the 3.9% difference reported for softwoods (guaiacyl lignin). Since Eucalyptus has more syringyl (S) than guaiacyl (G) units, this suggests that S units are overestimated in comparison to G units by analytical pyrolysis, in line with previous findings for different degradation methods, including pyrolysis.